Stable Isotopic Variability within Modern Travertines - Chafetz, Henry; Lawrence, James (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1994)
ABSTRACTSix hot and two ambient water travertine systems were sampled to determine the relationships between the stable isotopic composition of the travertines and the waters from which they were deposited. This was conducted in order to evaluate the use of geochemical analyses of ancient travertines for the interpretation of the composition of the waters from which they precipitated, climatic conditions at time of formation, etc. The waters displayed down-flow trends of progressively higher (^ 8'3C values, in all 8 systems, and (H) 618O values, in all 6 hot water systems. Whereas the stable isotopic values of the mineral precipitates sometimes showed similar trends, the magnitude of the downflow changes commonly was quite different than that exhibited by the water data. Additionally, different types of precipitates, which formed within centimeters of each other, commonly had different stable isotopic compositions, e.g., crusts which formed at the air/water interface always had higher 813C and 8'8O values than constituents which formed within the immediately subjacent water column. The lack of a simple relationship between stable isotopic composition of the water and the precipitate is due to the fact that the stable isotopic composition of the precipitates are controlled by a number of variables, including the water's composition, temperature, level of saturation, etc. And these variables can change dramatically within very short distances and at the same spot within very short time intervals. Thus, as demonstrated by the stable isotope data, attempting to interpret the composition of the water from the composition of the deposit is a highly risky venture.